2017
DOI: 10.1080/15384047.2017.1373211
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signature in the chemoprevention of functionally-enriched stem and progenitor pools (FESPP) by Active Hexose Correlated Compound (AHCC)

Abstract: These results support that AHCC limits FESPP growth, partly by targeting miRNA pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Our pioneering research in integrative oncology has shown that probiotic and prebiotic intake has tremendous immunoprotective and chemopreventative effects against breast cancer [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The underpinning mechanisms are thought to involve miRNAs and epigenetic-specific changes controlling breast cancer stem cells [ 25 ] and metastasis in vivo [ 22 , 26 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our pioneering research in integrative oncology has shown that probiotic and prebiotic intake has tremendous immunoprotective and chemopreventative effects against breast cancer [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The underpinning mechanisms are thought to involve miRNAs and epigenetic-specific changes controlling breast cancer stem cells [ 25 ] and metastasis in vivo [ 22 , 26 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 While no reports exist on the effect of Wasabi on CSC-derived mammospheres, a recently published article highlights the role of AHCC extracts to inhibit mammosphere growth in 3 cell lines. 47 Finally, when BAIC were provided to monocytes to understand whether such combination could concomitantly exert negative effects on immune cells, no cytotoxic effects were detected. Cell viability was found to be comparable to control groups in all experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…40 While no reports exist on the effect of Wasabi on CSC-derived mammospheres, a recently published article highlights the role of AHCC extracts to inhibit mammosphere growth in 3 cell lines. 47…”
Section: Discussionmentioning
confidence: 99%
“…ECLM was previously reported to have various anti-cancer effects via an immune-protective effect and through the regulation of miRNA expression [1][2][3][4][5]. ECLM is also known to reduce the risk of adverse neutrophil events in breast cancer patients who received adjuvant chemotherapy at 3 g/day oral administration [2].…”
Section: Discussionmentioning
confidence: 99%
“…A standardized extract of cultured Lentinula edodes mycelia (ECLM) is an extract from cultured Lentinula edodes that reportedly exerts immune-protective effects against many types of cancer, including liver, breast, colon, and prostate [1][2][3][4]. In a recent study, ECLM was also reported to suppress breast cancer stem cell proliferation by regulating the expression of microRNAs (miRNAs) [5,6]. These miRNAs are controlling genes involved in cellular processes such as inflammation, cell cycle regulation, stress response, differentiation, apoptosis, and migration [7].…”
Section: Introductionmentioning
confidence: 99%